2018
DOI: 10.1097/j.pain.0000000000001224
|View full text |Cite|
|
Sign up to set email alerts
|

Hyperpolarization-activated cyclic nucleotide–gated channels contribute to spontaneous activity in L4 C-fiber nociceptors, but not Aβ-non-nociceptors, after axotomy of L5-spinal nerve in the rat in vivo

Abstract: Peripheral neuropathic pain associated with partial nerve injury is believed to be driven partly by aberrant spontaneous activity (SA) in both injured and uninjured dorsal root ganglion (DRG) neurons. The underlying ionic mechanisms are not fully understood, but hyperpolarization-activated cyclic nucleotide-gated (HCN) channels which underlie the excitatory Ih current have been implicated in SA generation in axotomized A-fiber neurons after L5-spinal nerve ligation/axotomy (SNL/SNA). Here, using a modified mod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 61 publications
2
23
0
Order By: Relevance
“…The I h has been recognized to be carried by channels of the HCN gene family, namely HCN1, HCN2, HCN3 and HCN4 [10]. It has been recently demonstrated that HCN1, HCN2 or HCN3 channels play essential roles in sensory excitability and pain sensation [30,38,40]. Regardless of the detailed mechanism of their inhibitory actions, there is likely to be a relevant link between the effects of these croton derivatives on electrically excitable cells and their inhibitory effects on HCN channel activity, though croton-03-mediated effect on HCN channels might not be isoform-specific.…”
Section: Discussionmentioning
confidence: 99%
“…The I h has been recognized to be carried by channels of the HCN gene family, namely HCN1, HCN2, HCN3 and HCN4 [10]. It has been recently demonstrated that HCN1, HCN2 or HCN3 channels play essential roles in sensory excitability and pain sensation [30,38,40]. Regardless of the detailed mechanism of their inhibitory actions, there is likely to be a relevant link between the effects of these croton derivatives on electrically excitable cells and their inhibitory effects on HCN channel activity, though croton-03-mediated effect on HCN channels might not be isoform-specific.…”
Section: Discussionmentioning
confidence: 99%
“…This means finding a spontaneously firing neuron requires 4 or more successful experiments with at least 4 neurons in each experiment. Full details of the animal preparation were as reported previously (Djouhri et al, 2018). Briefly, to allow artificial ventilation and monitoring of end-tidal CO 2 , a tracheotomy was performed.…”
Section: In Vivo Electrophysiological Recordingsmentioning
confidence: 99%
“…The left jugular vein and carotid artery were tabulated to enable, respectively, regular injections of additional doses of anesthetic (sodium pentobaribtone 10mg/kg) and monitoring of blood pressure (normally ∼80-100 mmHg). A laminectomy was performed from vertebrae L2-L6 as reported previously (Djouhri et al, 2018). Intracellular voltage recordings from somata of L4 or L5 DRG neurons were obtained using sharp glass microelectrodes filled with 3M or 1M KCl.…”
Section: In Vivo Electrophysiological Recordingsmentioning
confidence: 99%
“…Intracellular recordings from DRG neurons both ex vivo and in vitro confirmed that peripheral nerve injury increases their excitability and may provoke spontaneous discharge of action potentials (Study and Kral, 1996;Djouhri et al, 2018). In a study of the effect of complete nerve section, we found and that the most profound increases were seen in animals that displayed autotomy (Abdulla and Smith, 2001a).…”
Section: Role Of Increased Peripheral Neuron Excitability and Dorsal mentioning
confidence: 59%